Effects of Temperature and Equivalence Ratio on Laminar Burning Speeds of α-Pinene/Benzene/Air Mixtures for Different Fuel Proportions. Issue 11 (1st December 2016) - Coudour, Bruno; Chetehouna, Khaled; Halter, Fabien; Mounaïm-Rousselle, Christine; Garo, Jean-Pierre
ABSTRACT: Sometimes forest fires have unpredictable and dangerous behaviors for human lives. One of these behaviors leads to accelerating forest fires, characterized by an augmentation of the rate of spread and of the energy released by the fire. The phenomenon mechanisms are not well understood but a thermochemical approach supports that volatile organic compounds coming from heated vegetation and smoke may create a flammable atmosphere near the fire front; according to the literature, α-pinene (C10 H16 ) and benzene (C6 H6 ) were found to be the main compounds. Therefore, we studied α-pinene/benzene/air mixtures by varying the initial temperature from 75°C to 180°C, equivalence ratio from 0.7 to 1.4, and fuel proportion. We focused on two combustion characteristics: laminar burning speeds and Markstein lengths. We observed a maximal laminar burning speed shifted from 1.1 equivalence ratio, when mixtures are rich in α-pinene, to 1.2, when mixtures are rich in benzene. With the increase of benzene percentage, laminar burning speeds also increase and the flame becomes more stable.